2015
DOI: 10.1155/2015/187849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Docosahexaenoic Supplementation andIn VitroVitamin C on the Oxidative and Inflammatory Neutrophil Response to Activation

Abstract: We studied the effects of diet supplementation with docosahexaenoic (DHA) and in vitro vitamin C (VitC) at physiological concentrations on oxidative and inflammatory neutrophil response to phorbol myristate acetate (PMA). Fifteen male footballers ingested a beverage enriched with DHA or a placebo for 8 weeks in a randomized double-blind study. Neutrophils were isolated from blood samples collected in basal conditions at the end of nutritional intervention. Neutrophils were cultured for 2 hours at 37°C in (a) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…It has been pointed out that exercise and ageing influence the degree of inflammation [48,49,50]. The present results showed that exercise, regardless of age or functional beverage supplementation, activates NFκβ in PBMCs that drives the cell to gene expression of pro-inflammatory cytokines, anti-oxidant enzymes and other genes [51,52]. The plasma levels of sL-selectin, sICAM3, Lipoxin, IL-6, TNFα, PGE2 are influenced by exercise [24,49], although their response to exercise are age and beverage dependent.…”
Section: Effects On Inflammatory Markersmentioning
confidence: 58%
“…It has been pointed out that exercise and ageing influence the degree of inflammation [48,49,50]. The present results showed that exercise, regardless of age or functional beverage supplementation, activates NFκβ in PBMCs that drives the cell to gene expression of pro-inflammatory cytokines, anti-oxidant enzymes and other genes [51,52]. The plasma levels of sL-selectin, sICAM3, Lipoxin, IL-6, TNFα, PGE2 are influenced by exercise [24,49], although their response to exercise are age and beverage dependent.…”
Section: Effects On Inflammatory Markersmentioning
confidence: 58%
“…This situation might probably reflect a lower basal ROS production by PBMCs as a result of the calorie restriction [16,49]. In fact, the expression of antioxidant enzymes is enhanced by ROS, such as hydrogen peroxide, in PBMCs [49], and this response is avoided by the antioxidant vitamin C in phorbol myristate acetate (PMA)-activated neutrophils [50]. Likewise, exercise training that enhances ROS production also increases the expression of HSP72 in PBMCs of premenopausal women [51].…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining a skeletal muscle involves an invasive procedure and for this reason various authors use erythrocyte FAs composition as an analogous measure to assess the efficacy of nutritional intervention trials to incorporate FAs into tissues [11, 24-26, 38, 50, 51]. Few studies compare muscle and erythrocyte FAs composition [16-19]; our research is, to the best of our knowledge, the first ever to compare the FAs composition of muscle and erythrocytes in adult humans in post-exercise conditions and after a CR period.…”
Section: Discussionmentioning
confidence: 99%